Binding of per- and polyfluoroalkyl substances (PFASs) to organic soil horizons of peat and mor : effect of solution chemistry and soil organic matter composition - Makselon, Jennifer (SLU/Dept. of Soil and Environment, 2019)
The understanding of sorption processes of per- and polyfluoroalkyl substances (PFASs) in soils is important for the determination of their fate and transport in the environment. The sorption behavior of PFASs of varying chain length and hydrophilic headgroup was studied in three organic soils, two peat soils and one mor layer, with differing chemical composition of the soil organic matter (SOM). PFAS sorption to the SOM of the peat samples was observed to be overall higher as compared to the mor sample, despite a higher amount of SOM in the latter. These results suggest that not only the quantity of SOM but also its quality pose an important parameter for PFAS binding. The effect of solution pH and added cation concentrations of Al3+ , Ca2+ and Na+ on sorption was investigated by performing batch sorption experiments and using ultra-high performance liquid chromatograph coupled to tandem mass spectroscopy (UHPLCMS/MS). The evaluation of the organic carbon-normalized partitioning coefficient (log KOC), showed that additions of Al3+ and Ca2+ yielded a higher sorption as compared to the addition of Na+ in all soils. Moreover, sorption was negatively correlated to the pH value. Thus, the results imply an inverse relationship to the net negative surface charge of the soils. Physico-chemical properties of PFASs, such as the hydrophilic head group and hydrophobic carbon tail, affected the sorption to SOM. Perfluorosulfonates (PFSAs) sorbed to a higher extent as compared to perfluorocarboxylates (PFCAs), while fluoroalkyl sulfonamides (FASAs) sorbed the strongest. The extent of PFAS sorption further increased with increasing perfluorocarbon chain length. In addition, specific binding mechanisms could not be observed in this present study and sorption isotherms were predominantly linear for aqueous concentrations ranging from ~1 to 130 ng mL -1 . Desorption of PFAS was further characterized to be concentration-dependent and negatively related to the compound hydrophobicity. Moreover, certain PFASs such as Et-FOSA and PFOA showed a hysteretic desorption behavior which further needs to be investigated.